Intrachiasmatic abscess caused by IgG4-related hypophysitis - Hadjigeorgiou, Georgios F.; Lund, Eva Løbner; Poulsgaard, Lars; Feldt-Rasmussen, Ulla; Rasmussen, Åse Krogh; Wegener, Marianne; Fugleholm, Kåre (Acta neurochirurgica, 2017)
Introduction Autoimmune hypophysitis is a rare disease of the pituitary, which may affect vision by inflammation and compression of the optic chiasm. However, intrachiasmatic abscess formation has not been previously reported. Methods In this study, we report a case of a 29-year-old female with bitemporal hemianopia due to a cystic intrasellar tumor. The patient underwent surgical decompression of the lesion, which was found to be an intrachiasmatic abscess. Results The histologic findings were consistent with IgG4 hypophysitis. Conclusion This rare clinical presentation suggests that in case of a disproportionate degree of visual impairment in relation to the size of the lesion, suspicion should lead to an intrachiasmatic lesion.